Contribution to the occupational risk assessment for sustainable management in health and safety at work: case study - ABDI, Meryem (Technium Business and Management, 2022)
This article describes the progress of continuous improvement of management practices based on feedback from adverse events revealed and recorded during a period of activity within a national company. This rapidly expanding tool is intended to provide the means for reflecting on the experience acquired during accidents and / or incidents that have occurred in a normal or disorganized situation, in order to draw the consequences, memorize it and reuse it. It is a process in which the manager observes with his own eyes the mapping of working conditions for a well-defined period and thus makes decisions based on real information. Thus, the assessment of occupational risks is at the heart of a search for continuous improvement in occupational health and safety. This assessment consists of a thorough inspection of the workplace to identifying the different situations and processes that may cause harm, in particular to people. It is very difficult to do prevention when we have a little knowledge of the factors that cause accidents or only part of them. To overcome these weaknesses and have an effective prevention in the company, a structured approach of action is proposed. The latter makes it possible to propose measures to improve performance in terms of health and safety and working conditions in companies. As a field of study, we try to constitute a memory of the risks based on the experience feedback of the adverse events manifested in the national company "SOFARE".